MYOSTATIN GENE ANALYSIS IN THE FIRST GENERATION OF THE BELGIAN BLUE CATTLE IN INDONESIA - Agung, P. P.; Said, S.; Sudiro, A. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
A study was conducted to identify the variations of the myostatin and also to evaluate the existence of genetic marker for “double muscling” (11-bp deletion in the third exon of the myostatin gene) in the first generation of Belgian Blue cattle in Indonesia using the Single Strand Conformation Polymorphism (SSCP) and the sequencing analysis. A total of 8 DNA samples belonged to Karya Anugerah Rumpin (KAR) Farm were used in the Single Strand Conformation Polymorphism (SSCP) and the sequencing analysis. There were 3 allele types of myostatin gene based on the SSCP analysis. The Belgian Blue sire has type A allele. The Simmental, Wagyu, SO x BX, Charolais, and the PO cattle have the type B allele, while the Belgian Blue x FH and the Belgian Blue x SO have the type C allele (heterozygous). There are 11-bp deletion in the third exon myostatin gene for the Belgian Blue sire based on the sequencing analysis. The myostatin gene in the Belgian Blue F1 generation individual was heterozygous. This study provides scientific evidence that the 11-bp deletion in the third exon of myostatin gene in the Belgian Blue sire was inherited to its F1 generation (male and female).